Library resource sharing solution based on federated authentication and CALIS unified authentication - Jie LV; Ping CHEN; Wen-qing WANG; Yang ZHANG; Bei ZHANG (Tongxin xuebao)
To address the problem of enforcing access control for library digital resources,federated authentication technologies were analyze which are widely used in the world,and CALIS unified authentication technologies that are widely deployed in China’s libraries were also analyzed.A solution integrating federated authentication and CALIS unified authentication technologies was proposed,which was developed,deployed and tested on the test-bed of CARSI federation.Test results show the proposed solution enforces effective and flexible access control for library resources.